"Double-Row" Suture for Achilles' Tendon Insercional Tendinopathy Reattachment and Two Types of Rehabilitation Protocol: A Retrospective Comparative Study. Issue 4 (November 2022) - Nery, Caio A.; Baumfeld, Tiago S.; Oliveira, Thiago B. Mafra; Baumfeld, Daniel
Category: Hindfoot Introduction/Purpose: The purpose of this Study is to evaluate the results of knotless double-row sutures for Achilles insercional tendinopathy reattachment and compare two types of post-operative rehabilitation protocols. Methods: This is a retrospective comparative study of collected data from patients who were treated in two different hospital by two different surgeons. Sixty-three (63) patients (66 feet) were included and separated in two different groups. All of them were submitted to the same technique for knotless double-row suture for Achilles insercional tendinopathy reattachment. Group 1 was treated with a functional rehabilitation at the end of a 4 weeks NWB period and group 2 with early and aggressive functional post- operative management. Results: We found that both types of post-operative regimen generate significant improvement in pain and functional scores. Regarding pain, both rehabilitation protocols generated similar results, with no statistically significant differences. However, the FAAM-AVD score, on average, of patients in Group 1 was slightly higher than that of patients in the Group 2. This means that more than 50% of patients in the group 1 had a higher FAAM-AVD than all patients in the group 2. Regarding the comparison of the postoperative rehabilitation of the groups, a more accentuated improvement was observed in the group where functional rehabilitation was postponed to the 5th post-operative week, and the patients having remained immobilized for 4 (four) weeks in a NWB suropodalic orthosis on the operated limb. Conclusion: The double-row suture system for Achilles' reattachment is an excellent option for the surgical treatment of insertional Achilles' tendinopathy. The functional outcome of patients who were submitted to a 4-week delayed functional rehabilitation program is slightly better than those submitted to an early and aggressive functional rehabilitation program.